Perancangan dan Penerapan Websıte Company Profıle dan Pemesanan pada PT Ferwındo Karya Pratama - Yefta Christian; Meiliverani Erline (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
PT Ferwindo Karya Pratama is a company which has been operating for almost 3 years and enganged in procuring and supplying all kind of need for local industries. One of the significant obstacles experienced by PT Ferwindo Karya Pratama since its official establishment was that there was no company profile and online ordering system that could simultaneously function as promotional media and product ordering media automatically. In addition to making it easier for clients and prospective clients to get the latest and complete information, this system also makes it easier for ordering from anywhere and anytime online. This study uses the System Development Life Cycle system development methodology with the Waterfall model. The final result of this study is the web-based company profile with ordering feature and integrated with an admin page to manage web content. This research is implemented with the hope that the system can become a media promotion for the company so that people can easily access actual information about the company and place an order, so as to increase the sales of PT Ferwindo Karya Pratama